PENGARUH PELAYANAN PRIMA DAN HARGA TERHADAP LOYALITAS PELANGGAN (Studi pada Pelanggan Layanan PT. Pos Indonesia Semarang) - Fajar Andrianto Saputra; Hari Susanta Nugraha; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
This research is motivatedany decrease in the number of customers by PT. Pos Indonesia. Because the customers are less satisfied with respect to the service provided by PT Pos Indonesia so many customers who move to other delivery services. The purpose of doing research is to figure out how big the influence of excellent service and price to customer loyalty, PT. Pos Indonesia. Sampling techniques using non probability sampling with the kind of purposive sampling. The respondents in this study amounts to 100 respondents. The analysis used in a research is quantitative analysis using the software SPSS 20.0 for Windows Evaluatin Version, where previously done test validity, reliability, cross-tab, the coefficient of correlation, simple and multiple regression analysis, the coefficient of determination, test of significance (t-test and F-test) in advance. The results of research show that excellent service (X1) and price (X2) partially or simultaneous affect customer loyalty (Y).